PENERAPAN SIKADESTROPIK UNTUK PENCEGAHAN PENYAKIT KATASTROPIK BAGI KADER POSYANDU LANSIA DESA WIRU KECAMATAN BRINGIN KABUPATEN SEMARANG - Sari, Devi Pramita; Nabilatul Fanny; Fifi Anisa Nur Hidayati (GEMASSIKA: Jurnal Pengabdian Kepada Masyarakat, 2024)
Catastrophic disease is a disease that requires long and high cost medical treatment. Diseases included in the catastrophic group include hypertension, diabetes mellitus, and stroke. In the preliminary study it was found that those with catastrophic diseases were also a group that received serious attention from elderly posyandu cadres in Wiru Village because 366 elderly people in Wiru Village suffered from catastrophic diseases, 305 elderly people had a low economic level out of a total of 610 elderly people, lack of adequate treatment optimal results from elderly and village posyandu cadres, and it is known that the lack of training obtained by elderly posyandu cadres for knowledge related to catastrophic diseases. The purpose of this PkM activity is to increase the knowledge of elderly posyandu cadres through digital-based education by implementing the Catastrophic Hospital Calculator Information System (SIKADESTROPIK). This is what underlies the holding of community service with the title "Implementation of SIKADESTROPIK for the Prevention of Catastrophic Diseases for Elderly Posyandu Cadres in Wiru Village, Bringin District, Semarang Regency". The activity phase begins with coordination and communication activities with the Chairperson of the Posyandu Cadre in Wiru Village and the Head of the Elderly Posyandu Cadre in Wiru Village. Implementation of Community Service (PKM) is carried out offline through digital-based education. The output of this PkM activity is the publication of scientific articles in PkM journals, HKI, 5-minute videos of PkM activities, and integration of the results of PkM activities into courses. The outputs of this PkM are expected to have an impact on increasing knowledge, increasing the quality of skills, as well as the real practice of Posyandu Cadres for the Elderly in Wiru Village, Bringin District, Semarang Regency for digital-based catastrophic disease prevention. Keywords: Stunting Cadre Education, Digital Based, Brainstorming Method